The impact of financial literacy on the sustainability of female entrepreneurship in the Namibian sosmetic industry (Namibian Journal for Research, Science and Technology, 2024)
This paper analyses the impact of financial literacy on the sustainability of female entrepreneurship in the Namibian cosmetic industry. The aim of the study was to identify the financial literacy challenges faced by female entrepreneurs in Namibia when managing their businesses, analyse these challenges, and propose possible solutions. Previous studies have focused either on the overall financial literacy of the Namibian adult population or on the financial literacy of SMEs in general. This study therefore investigated the impact of financial literacy skills on the sustainability of female-run enterprises within the Namibian cosmetic industry. The study adopted a correlational research design, and the data were analysed using STATA 15 statistical software. The results confirmed that most entrepreneurs in Namibia are young, female and, for the most part, educated. However, the findings revealed that, despite their relatively high levels of education, female entrepreneurs still lack the necessary financial literacy skills. For example, female entrepreneurs had lower financial literacy skills than their male counterparts, which has negatively affected the sustainability of their businesses over the years. The study recommends that, as a matter of urgency, the Namibian cosmetic industry and other interested stakeholders make concerted efforts to provide financial literacy education to female entrepreneurs. Such training would equip them with the financial literacy skills needed to improve the sustainability of their enterprises.
Keywords: Entrepreneurship; Female entrepreneurs; Financial literacy; Impact; Sustainability